2016
DOI: 10.1179/1743281215y.0000000030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluxing agents on reduction degradation behaviour of hematite pellets

Abstract: During induration at a high temperature, a considerable amount of slag/melt phase forms inside the iron ore pellets, comprising SiO 2 , Al 2 O 3 , CaO, MgO and FeO. After cooling, the slag phase solidifies and acts as an important bonding phase in the finished pellets and influences their room temperature as well as high temperature properties, especially reduction degradation. Fluxing agents play an important role in forming these bonding phases depending on the type and amount of flux. In the present study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The large-scale utilization of high basicity sinter is based on its high reducibility and good softening performance [53]. Generally speaking, the reducibility of acid pellets is poor [54,55], while the reducibility of MgO-bearing pellets has been improved to a considerable extent [56][57][58]. The addition of MgO improves the reducibility of pellets, while excessive MgO produces silicate melt in the reduction process, which is not good for reducibility.…”
Section: Reducibilitymentioning
confidence: 99%
“…The large-scale utilization of high basicity sinter is based on its high reducibility and good softening performance [53]. Generally speaking, the reducibility of acid pellets is poor [54,55], while the reducibility of MgO-bearing pellets has been improved to a considerable extent [56][57][58]. The addition of MgO improves the reducibility of pellets, while excessive MgO produces silicate melt in the reduction process, which is not good for reducibility.…”
Section: Reducibilitymentioning
confidence: 99%
“…And the preheating time was also found to play an important role in the extent of oxidation and calcination. Dwarapudi et al [9,10] studied carbon-containing fluxed pellets in the range of basicity (CaO/SiO 2 ) (0–0.8) and MgO content (0–1.5) and the effect of pellet basicity (CaO/SiO 2 ) and MgO content on pellet quality during hardening. And microstructure effects.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have prepared pellet by adding different types of additives, such as dolomite, light burned dolomite, magnesium fines, high magnesium olivine and so on [9][10][11][12]. Dwarapudi et al [13][14][15][16] studied the effect of MgO source, MgO content and basicity on the reducing performance of hematite pellets, such as reduction swelling index, reducibility and microstructure, and found that RSI could be promoted with the addition of MgO. A series of works had also been done by to investigate the addition of magnesium olivine on the reduction behaviour of magnetite pellets and interaction between iron ore and olivine under different temperatures.…”
Section: Introductionmentioning
confidence: 99%